STUDI TENTANG TRAVELLING SALESMAN DAN VEHICLE ROUTING PROBLEM DENGAN TIME WINDOWS - I Nyoman Sutapa; I Gede Agus Widyadana; Christine Christine (Institute of Research and Community Outreach - Petra Christian University, 2003)
The article shows the study of model development of travelling salesman problem. Three models are studied, i.e. travelling salesman problem with time windows, vehicle routing problem, and vehicle routing problem with time windows. Abstract in Bahasa Indonesia : Dalam artikel ini dipaparkan kajian mengenai pengembangan model travelling salesman problem. Ada tiga model yang dikaji yaitu travelling salesman problem dengan time windows, vehicle routing problem, serta vehicle routing problem dengan time windows. Kata-kunci: travelling salesman problem, vehicle routing problem, time windows.